StaTips Part III: Assessment of the repeatability and rater agreement for nominal and ordinal data - Perinetti, Giuseppe (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Assessment of the repeatability and rater agreement for nominal and ordinal data is an important procedure in medical research. This analysis applies to several cases including: i) replicate recordings by the same rater using the same parameter; ii) agreement between/among raters using the same parameter; and iii) agreement between/among different parameters recorded by the same rater. Herein, the most common coefficients of agreement are presented along with criteria for their proper selection.